Distribution of Cortical Diffusion Tensor Imaging Changes in Multiple Sclerosis - Stock, Benjamin; Shrestha, Manoj; Seiler, Alexander; Foerch, Christian; Hattingen, Elke; Steinmetz, Helmuth; Deichmann, Ralf; Wagner, Marlies; Gracien, René-Maxime (Frontiers in Physiology, 2020)
Purpose: Diffuse cortical damage in relapsing-remitting multiple sclerosis (RRMS) is clinically relevant, but cannot be directly assessed with conventional MRI. In this study, it was aimed to use diffusion tensor imaging (DTI) techniques with optimized intrinsic eddy current compensation to quantify and characterize cortical mean diffusivity (MD) and fractional anisotropy (FA) changes in RRMS and to analyse the distribution of these changes across the cortex. Materials and Methods: 3 T MRI acquisition, mapping of the MD providing information about the integrity of microstructural barriers and of the FA reflecting axonal density and surface-based analysis with Freesurfer were performed for 24 RRMS patients and 25 control subjects. Results: Across the whole cortex, MD was increased in patients (p < 0.001), while surface-based analysis revealed focal cortical FA decreases. MD and FA changes were distributed inhomogeneously across the cortex, MD increase being more widespread than FA decrease. Cortical MD correlated with the Expanded Disability Status Scale (EDSS, r = 0.38, p = 0.03). Conclusions: Damage of microstructural barriers occurs inhomogeneously across the cortex in RRMS and might be spatially more widespread than axonal degeneration. The results and, in particular, the correlation with the clinical status indicate that DTI might be a promising technique for the monitoring of cortical damage under treatment in larger clinical studies.